The Genetic Analysis of an Acinetobacter johnsonii Clinical Strain Evidenced the Presence of Horizontal Genetic Transfer - Montaña, Sabrina Daiana (2016)
Acinetobacter johnsonii rarely causes human infections. While most A. johnsonii isolates are susceptible to virtually all antibiotics, strains harboring a variety of β-lactamases have recently been described. An A. johnsonii Aj2199 clinical strain recovered from a hospital in Buenos Aires produces PER-2 and OXA-58. We decided to delve into its genome by obtaining the whole genome sequence of the Aj2199 strain. Genome comparison studies on Aj2199 revealed 240 unique genes and a close relation to strain WJ10621, isolated from the urine of a patient in China. Genomic analysis showed evidence of horizontal genetic transfer (HGT) events. Forty-five insertion sequences and two intact prophages were found in addition to several resistance determinants such as blaPER-2, blaOXA-58, blaTEM-1, strA, strB, ereA, sul1, aacC2 and a new variant of blaOXA-211, called blaOXA-498. In particular, blaPER-2 and blaTEM-1 are present within the typical contexts previously described in the Enterobacteriaceae family. These results suggest that A. johnsonii actively acquires exogenous DNA from other bacterial species and concomitantly becomes a reservoir of resistance genes.